Blood concentrations of tacrolimus upon conversion from rabeprazole to vonoprazan in renal transplant recipients: Correlation with cytochrome P450 gene polymorphisms. (October 2021) - Watari, Shogo; Araki, Motoo; Matsumoto, Jun; Yoshinaga, Kasumi; Sekito, Takanori; Maruyama, Yuki; Mitsui, Yosuke; Sadahira, Takuya; Kubota, Risa; Nishimura, Shingo; Wada, Koichiro; Kobayashi, Yasuyuki; et al.
Abstract: We evaluated the impact of vonoprazan on blood concentrations of tacrolimus via a retrospective analysis of 52 renal transplant recipients who took tacrolimus and converted from rabeprazole to vonoprazan between August 2018 and September 2019. We compared tacrolimus trough levels upon conversion among groups that were classified based on cytochrome P450 (CYP) gene polymorphisms. CYP3A5 groups were heterozygous or homozygous for CYP3A5∗1 and CYP3A5∗3 alleles. CYP2C19 genotypes were classified as extensive ( ∗1/∗1), intermediate ( ∗1/∗2 and ∗1/∗3 ) or poor metabolizers ( ∗2/∗2, ∗2/∗3 and ∗3/∗3 ). Tacrolimus trough levels increased only 0.3 ng/mL upon conversion in the CYP3A5∗3/∗3 group: 5.8 [3.4-7.2] vs 6.1 [3.8-7.9]; p  = 0.06. No statistically significance changes in tacrolimus levels also occurred in the CYP3A5∗1/∗1 or CYP3A5∗1/∗3 groups. Subgroup analyses of CYP3A5∗3/∗3 demonstrated low changes for all three CYP2C19 subgroups: 5.2 [4.3-6.5] vs 6.2 [4.3-7.9]; p  = 0.07, 6.1 [3.4-7.2] vs 6.7 [4.6-7.9]; p  = 0.12 and 5.4 [3.6-6.5] vs 4.7 [3.8-6.3]; p  = 1.00, respectively. Conversion to vonoprazan thus resulted in little increase of tacrolimus trough levels, even in the group predicted to be most susceptible ( CYP3A5∗3/∗3 and 2C19∗1/∗1 ), thus supporting the safety of concomitant use of vonoprazan with tacrolimus.